Interactive TV system - 253847 Azlan Yusof; Norbik Bashah Idris; Centre for Advanced Software Engineering (CASE) (2002)
Thesis (Sarjana Sains (Real Time Software Engineering)) - Universiti Teknologi Malaysia, 2002